2016
DOI: 10.1556/004.2016.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biomarkers following autologous osteochondral transplantation in the equine stifle joint — An experimental study

Abstract: The purpose of this study was to evaluate changes in biomarker and synovial parameters following autologous osteochondral transplantation (AOT) in the equine stifle joint, to test the hypothesis whether synovial parameters would show significant differences at selected time points following the surgery (at days 3, 14, 60 and 180) compared to baseline level (at day 0). Surgical intervention was performed in both stifles of nine horses (n = 18). The joints were randomly assigned to operated and sham-operated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Arthroscopic mosaic arthroplasty or mosaicplasty is commonly used in human surgery to repair large chondral defects by harvesting osteochondral grafts from non-weight-bearing areas and transplanting them to the affected site. This approach has been experimentally evaluated in the equine radiocarpal, metacarpophalangeal and femoropatellar joints [28]. In one study, three osteochondral grafts were harvested arthroscopically from the femoropatellar joint and transplanted to the third carpal bone.…”
Section: Mosaicplastymentioning
confidence: 99%
See 2 more Smart Citations
“…Arthroscopic mosaic arthroplasty or mosaicplasty is commonly used in human surgery to repair large chondral defects by harvesting osteochondral grafts from non-weight-bearing areas and transplanting them to the affected site. This approach has been experimentally evaluated in the equine radiocarpal, metacarpophalangeal and femoropatellar joints [28]. In one study, three osteochondral grafts were harvested arthroscopically from the femoropatellar joint and transplanted to the third carpal bone.…”
Section: Mosaicplastymentioning
confidence: 99%
“…Nine months after the operation, the osteochondral grafts in the third carpal bone had less proteoglycans, leaving the cartilage softer and less resistant compared to the surrounding cartilage. Six of 18 grafts had histological evidence of cartilage degeneration and it was suggested that the discrepancy in cartilage thickness as well as chondrocyte phenotypic expression between the donor and recipient sites was a major limitation to obtaining functional osteochondral integration [28].…”
Section: Mosaicplastymentioning
confidence: 99%
See 1 more Smart Citation